Mobile Learning for Manually Coded Malay Sign Language using Augmented Reality - Abdul Razak, Raz Nur Izzaty; Senan, Norhalina (Applied Information Technology And Computer Science, 2022)
Deaf children have difficulty in reading comprehension and are significantly lagging in education as compared to their hearing peers. This can affect their communication skills and in turn affect their academic achievement. However, the existing application developed for sign language education have a few drawbacks such as it only consists of learning module and the media used was only learning videos. Hence, the Mobile Learning for Manually Coded Malay Sign Language using Augmented Reality (KTBM AR) is developed to provide users with learning and activity modules where users can interact with and test their knowledge. Not only that, KTBM AR also included Augmented Reality (AR) as interactive learning medium to engage users more into learning. The methodology used in developing this application is ADDIE model which comprises five main phases which are analysis, design, development, implementation and evaluation phase. The result from testing shows that the application was successfully developed with a range of 86.80% acceptable according to System Usability Scale (SUS). Thus, it can be concluded that KTBM AR is suitable to be implemented in sign language learning.